Implementasi Acara Bengkel Literasi Generasi Muda: Penulisan Puisi bagi Mahasiswa terhadap Mahasiswa Magang di Balai Bahasa Jawa Tengah - Abel Wulandari Kusuma Putri; Rizkyna Fatul Yaumi; Dionysius Nazario Daffa Setiaji; Rahsiwi Bitristan Pamungkas; Friskila Yesika Noveliah; Katharina Rustipa (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
In response to the lack of enthusiasm among students for writing poetry, the Central Java Language Center organized a Young Generation Literacy Workshop: Student Poetry Writing event. The primary goal of this workshop was to train aspiring students in the art of creating poetic literary works and to enhance their proficiency in writing according to the EYD (Ejaan Yang Disempurnakan) guidelines. In this study, we employed a qualitative descriptive approach to elucidate a phenomenon that arose following students' participation in the Young Generation Literacy Workshop: Poetry Writing for Students during their internships at the Central Java Language Center. The activity's outcomes consist of participants' poetry in pdf format. Furthermore, these exercises provide students with the opportunity to acquire fresh knowledge, allowing them to analyze poetry, grasp its linguistic components, improve their skills in creative writing, and develop a more profound comprehension of language and literature principles.